(untitled) (Research, Society and Development, 2020)
One of the dairy products derived from goat milk that has been gaining prominence in the industrial sector is Coalho cheese, and the addition of marmeleiro flour may be an alternative to add value to this product. Thus, the objective of this research was to evaluate along the cold storage the physical-chemical, functional, microbiological and sensory acceptance of the goat’s milk curd with 0.12% and 0.18% of marmeleiro flour. Refrigerated storage time significantly influenced acidity, pH, proteolysis, soluble calcium, free oil and color. Marmeleiro concentration affected proteolysis and pH, while the interaction between the addition of different marmeleiro concentrations and storage time interfered with proteolysis, melt and luminosity. The cheeses presented microbiological results according to current legislation, being suitable for the human consumption. The results of the sensory evaluation for the attributes appearance, color, aroma, taste, texture and global acceptance did not present significant differences between the formulations analyzed, being good acceptance, however there was a statistical difference for the purchase intention test. seasoned cheese with 0.18% quince most preferred by reviewers. In this context, the results showed a viable alternative for the food industry, both by adding value to the product through the addition of marmeleiro, and by the stability of the product throughout the cold storage.